Lettere Alle Tre Amiche. - Slataper, Scipio; Caliaro, Ilvano; Favero, Marco; Norbedo, Roberto; Slataper, Scipio; Caliaro, Ilvano; Favero, Marco; Norbedo, Roberto (Berlin/Boston : Walter de Gruyter GmbH, 2022)
The volumes published in this series analyze literary and cinematic narrations from the Alpe Adria region and the Mediterranean. The literary, visual, historical, cultural, and inguistic dynamics which characterize these areas play an essential, multifaceted role in their various manifestations, past and present. Against this backdrop, the term "border" becomes a highly complex, volatile concept.
Intro -- Indice -- Introduzione -- Cronologia -- Nota sul testo -- Tavola delle abbreviazioni -- Alle "tre amiche" -- Lettere ad Anna (1910) -- 1910 -- Lettere ad Elody (1909-1915) -- 1909 -- 1910 -- 1911 -- 1912 -- 1913 -- 1914 -- 1915 -- Lettere a Gigetta (1909-1915) -- 1909 -- 1910 -- 1911 -- 1912 -- 1913 -- 1914 -- 1915 -- Indice dei nomi.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books